Macroeconomic uncertainty and real investment in Colombia - Posada Duque, Héctor Mauricio (Sociedad y Economía, 2010)
This paper empirically examines the relationship between macroeconomic uncertainty and aggregate real investment in Colombia during the first quarter of 1994 and the fourth quarter of 2006. To do this, first, we build a measure of uncertainty using a model of time-changing parameters, a GARCH model and principal component analysis, then, we estimate a equation for the rate of investment growth using the instrumental variables method. The results suggest that macroeconomic uncertainty has a negative effect on the rate of investment growth, providing new evidence in favor of the theories of irreversible investment under uncertainty, and showing a mechanism that probably made the crisis of 99 in Colombia worse.